Voices of Resilience from the Bottom Rungs: The Stories of Three Elementary Core French Teachers in Ontario - Knouzi, Ibtissem; Mady, Callie (Alberta Journal of Educational Research, 2014)
This paper reports on a study that used activity theory (AT) as a framework to understand the dialogical relationship between three elementary Core French (CF) teachers’ personal and professional experiences and their literacy teaching beliefs and practices. This study used a case study design collecting data from three different teachers in three different locations by means of semi-structured interviews to help capture teachers’ perspective of their professional experiences. The interviews exposed the teachers’ creativity in dealing with concerns about their personal and professional goals and (limited) resources available, documented facilitating or constraining effects on the community that operated within the same activity system, and identified unspoken agendas of their wider professional communities. The analysis of the teachers’ narratives reveals that the definition of the status and role of CF within the Canadian educational context is an essential source of tension that affects the teachers’ teaching practices and their sense of professional identity. Cet article porte sur une étude ayant comme cadre la théorie de l’activité pour comprendre le rapport dialogique entre les expériences personnelles et professionnelles de trois enseignantes de français de base à l’élémentaire d’une part, et leurs croyances et pratiques par rapport à l’enseignement de la littératie d’autre part. Cette étude repose sur modèle d’étude de cas et a impliqué la collecte de données par le biais d’entrevues semi-structurées auprès de trois enseignants différents dans trois lieux différents de sorte à obtenir leur point de vue quant à leurs expériences professionnelles. Les entrevues ont révélé la créativité des enseignants face à leurs préoccupations relatives à leurs buts personnels et professionnels et les ressources limitées disponibles; documenté les effets facilitateurs ou restrictifs sur la communauté qui fonctionnait au sein du même système d’activités; et identifié les intentions tacites de leurs communautés professionnelles élargies. L’analyse des récits des enseignants a démontré que la définition du statut et du rôle du français de base dans le milieu éducatif Canadien est une source de tension qui affecte leurs pratiques pédagogiques ainsi que le sens de leur identité professionnelle.